Development Individual Work Activity Report Information System at PT. Ayub Pri Tower Kreasi Website based - Dimas Putra Ramadhan Mendrofa; Hardiansyah Putra; Abdul Khaliq (Bahasa Indonesia, 2026)
PT. Ayub Pri Tower Kreasi operates in the construction and network installation services sector. Based on interviews and observations, work activity reporting is still done manually after the job is completed and by only one person. This creates obstacles such as a lack of information, potential reporting errors, and difficulties in storing and retrieval of historical data. As a result, management does not obtain accurate and real-time information on employee work activities, hampering decision-making and employee performance evaluation. Therefore, this research aims to develop a web-based individual work activity information reporting system. This system is expected to assist management in operations, support decision-making, improve performance, and ensure the accountability of each employee. Through the data and information from the developed system, company management can make effective decisions, conduct evaluations and assess management strategies, and ensure each technician/employee's performance. The system was developed using the waterfall method, which includes analysis, design, implementation, testing, and maintenance. System testing was conducted using black box testing to ensure system functions operate as required.